2020
DOI: 10.3389/fpsyg.2020.00604
|View full text |Cite
|
Sign up to set email alerts
|

The “Managed” or Damaged Heart? Emotional Labor, Gender, and Posttraumatic Stressors Predict Workplace Event-Related Acute Changes in Cortisol, Oxytocin, and Heart Rate Variability

Abstract: Vital to the everyday operation of police services, police communicators (911 call-takers and dispatchers) are persistently subject to imminent challenges in the workplace; they must always be prepared to engage and deal with a wide variety of circumstances that provoke various intense emotions and physiological stress responses. Acute changes in cortisol, oxytocin, and heart rate variability are central to adaptive responses in stressful complex social interactions, but they might also be indicative of physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 136 publications
0
19
0
Order By: Relevance
“…In this study we used retrospective self-reported data, thus we cannot exclude the possibility that our findings were influenced by monomethod bias (Mueller & Tschan, 2011) Birze et al, 2020;Regehr, 2018). The finding that the average seniority of employees in the department positively predicted PTSD and somatic symptoms, signals the possible influence of repeated exposure to WPA, also reported elsewhere (Lamothe et al, 2021;Pihl-Thingvad et al, 2019;Regehr, 2018).…”
Section: Limitations and Future Directionsmentioning
confidence: 80%
See 2 more Smart Citations
“…In this study we used retrospective self-reported data, thus we cannot exclude the possibility that our findings were influenced by monomethod bias (Mueller & Tschan, 2011) Birze et al, 2020;Regehr, 2018). The finding that the average seniority of employees in the department positively predicted PTSD and somatic symptoms, signals the possible influence of repeated exposure to WPA, also reported elsewhere (Lamothe et al, 2021;Pihl-Thingvad et al, 2019;Regehr, 2018).…”
Section: Limitations and Future Directionsmentioning
confidence: 80%
“…diagnoses of illness) or physiological stress responses (e.g. changes in cortisol, oxytocin and heart rate; Birze et al., 2020; Regehr, 2018). The finding that the average seniority of employees in the department positively predicted PTSD and somatic symptoms, signals the possible influence of repeated exposure to WPA, also reported elsewhere (Lamothe et al., 2021; Pihl‐Thingvad et al., 2019; Regehr, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results revealed that those who felt greater emotional dissonance (i.e., being mistreated by a customer when having positive display rules) experienced heightened blood pressure. More recently, a study of 911 call‐takers and dispatchers found that after controlling for trauma from events, deep acting reduced event‐based cortisol spikes, while surface acting was unrelated (Birze et al., 2020), contributing to the well‐being puzzle associated with deep acting.…”
Section: Current Decade Of Expansion Of Emotional Labor Research (201...mentioning
confidence: 99%
“…This can be supported by Neufeld et al, (2016) who found that emergency personnel had reduced HRV as a result of reduced and disrupted sleep on workdays. Despite these findings, recent research identifies an association between increased HRV and chronic stress, suggesting decreases in the HF/LF ratio are based on acute stressors (Birze et al, 2020;Balzarroti et al, 2017). This therefore would therefore suggest emergency personnel are predisposed to increased HRV due to the chronic stress they face in the workplace (Donnelly et al, 2016;Langan-Fox et al, 2011).…”
Section: Physiological Indicatorsmentioning
confidence: 99%